2016
DOI: 10.1136/bjophthalmol-2016-308685
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric characterisation of pterygium associated with corneal stromal scarring using high-resolution anterior segment optical coherence tomography

Abstract: HR-ASOCT is a useful tool for the assessment and monitoring of pterygia in clinical practice. Features associated with increased stromal scarring and astigmatism are reduced thickness of the head of the pterygium and flat bridging of the corneoscleral transition zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 13 publications
2
25
0
Order By: Relevance
“…These findings could be explained by the diversity of pterygium characteristics in our study, considering a large number of eyes with pterygium were included. Various characteristics of pterygium might have diverse effects on corneal astigmatism and subepithelial irregularities 18…”
Section: Discussionmentioning
confidence: 99%
“…These findings could be explained by the diversity of pterygium characteristics in our study, considering a large number of eyes with pterygium were included. Various characteristics of pterygium might have diverse effects on corneal astigmatism and subepithelial irregularities 18…”
Section: Discussionmentioning
confidence: 99%
“…Applications of AS-OCT in corneal disease are wide and clinically well established. This includes evaluation of pterygium [102], management guidance in ocular surface neoplasia [103], characterization of abnormalities associated with keratoconus [104-108], and evaluation of corneal wound healing [109-113]. The role of AS-OCT is also important in preoperative, intraoperative, and postoperative assessment of patients requiring corneal surgeries [111, 114-118].…”
Section: Imaging and Ne(ur)ovascularizationmentioning
confidence: 99%
“…As such, it is most commonly seen in populations working outdoors or living in tropical climates. Studies have shown that apart from causing corneal surface changes, 5,6 pterygium may also be associated with degradation of Bowman's layer and stromal scarring 7,8 due to activation of cell proliferation factors, inflammatory mediators, growth factors, extracellular matrix modulators and angiogenic factors. 9 Theoretically, these mediators and UV light may also damage deeper corneal endothelial cells (ECC) and thus corneal endothelial cell density (ECD) may be decreased in eyes with pterygium.…”
Section: -4mentioning
confidence: 99%